Disruption Of Family Relationships And Their Consequences (Global Scientific Review, 2024)
In the process of spiritual and moral reforms being implemented in society, based on the specific characteristics of Uzbek families, the specific place, role and importance of family education in resolving family conflicts are determined by clarifying, enriching and studying the spiritual and educational content of family education relations